Problematika Pendidikan Agama Islam di Sekolah Umum Tingkat SMA - Fathurrahman, Fathurrahman; Pulungan, Syaiful Hadi; Munastiwi, Erni (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2020)
Nowdays the problem of moral decadence among students is increasingly concerning. Therefore, character education in the school is very important to be implemented. This study aims to describe and analysis the urgency of the implementation of character education to answer the moral decadence in SMA Al-Ulum Terpadu Medan. This study uses a qualitative method. Observations, interviews and documentation are applied in order to find facts in the field. The results of this study indicate that the practice and inculcation of characters in Al-Ulum Integrated High School Medan is carried out through intra and extracurricular activities by touching the cognitive, affective, and psychomotor domains of students who are supported by cooperative employees in displaying good character in school. In addition, internalizing character education requires collaboration with various parties so that the realization of character values ​​can be achieved in order to build a better human civilization.